Estudio de transferencia de inmunidad en crianzas artificiales de terneros en la cuenca lechera santafecina - Aguirre, F. (2019)
The new-born calf depends on the passive immunity acquired through the consumption of colostrum to fight against pathogens present in the environment. In this study we proposed to quantify the efficiency of the immunity transfer through colostrum in calves in commercial dairies in Santa Fe province and to correlate the results to mortality. Serum samples from 2418 animals were assessed for proteins by means of a refractometer (indirect indicator of immunity transference). 57,4% of animals resulted with ?good? immunity transfer (group A:?5,5 g/dl), 22,7% had a ?medium? transfer (group B: ? 5 g/dl and < 5,5 g/dl) and 19,8% had a ?poor? immunity transfer (group C: < 5 g/dl). Calves with ?poor? immunity transfer had 3,14 times more probabilities to die before 60 days old than animals with a ?good? colostrum. We did not notice that calves from primiparus cows or those born from a dystocic parturition had less inmunity transfer results. More research is needed to evaluate other variables that could influence calf mortality in artificial rearing systems.